You Want it Sweeter: How Glycosylation Affects Plant Response to Oxidative Stress - Behr, Marc; Neutelings, Godfrey; El Jaziri, Mondher; Baucher, Marie (Frontiers in Plant Science, 2020)
Oxidative stress is a cellular threat which put at risk the productivity of most of crops valorized by humankind in terms of food, feed, biomaterial or bioenergy. It is therefore of crucial importance to understand the mechanisms by which plants mitigate the deleterious effects of oxidizing agents. Glycosylation of antioxidant molecules and phytohormones modifies their chemical properties as well as their cellular and histological repartition. This review emphasizes the mechanisms and the outcomes of this conjugation reaction on plant ability to face growing conditions favoring oxidative stress, in mirror with the activity of deglycosylating enzymes. Pioneer evidence bridging flavonoid, glycosylation and redox homeostasis paved the way for numerous functional analyses of UDP-glycosyltransferases (UGTs), such as the identification of their substrates and their role to circumvent oxidative stress resulting from various environmental challenges. (De)glycosylation appears as a simple chemical reaction regulating the biosynthesis and/or the activity of a myriad of specialized metabolites partaking in response to pathogen and abiotic stresses. This outcome underlies the possibility to valorize UGTs potential to upgrade plant adaptation and fitness in a rising context of sub-optimal growing conditions subsequent to climate change.